(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this paper author is trying to review various techniques presented so far. In the coming days home automation system (HAS), has gain popularity not only in foreign countries but also in metro politician cities of India. In these paper three different aspects of home automation system is reviewed and commented. The various researches have worked on HAS by using different methods e.g. Bluetooth technology, internet based service (android application) and wireless sensor network. This paper will review all techniques mentioned above and will try to analyze the factors affecting them in upcoming research.